A CFD-based scaling approach for ducted propellers. (1st September 2016) - Bhattacharyya, Anirban; Krasilnikov, Vladimir; Steen, Sverre
Abstract: This paper addresses the problem of scale effect on the open water characteristics of ducted propellers. Based on systematic CFD calculations performed at different Reynolds numbers, a scaling approach is proposed for practical use. A controllable-pitch propeller working within two ducts of different design- the standard Duct 19A, and an innovative duct concept Innoduct10 proposed by Rolls-Royce, have been considered as the main target cases. Scale effects predicted on the pressure and friction components of propeller thrust and torque coefficients and duct thrust coefficients are compounded into a component-based scaling procedure using individual scaling functions. While the principal focus has been on the range of operation conditions from trawling to free-sailing, other critical conditions such as bollard and high advance coefficients are also discussed. The same propeller is also studied in open conditions (without duct) in order to understand the difference in the mechanisms underlying scale effects between ducted and open propellers. The applicability of the developed scaling approach is discussed using two different propulsor cases. The scaling procedure can be used to obtain the full scale open water diagram for ducted propellers from the results of open water tests conducted in model scale, without the need for new CFD computations in each case. Although the use of the developed scaling method on the test propeller shows good results, more test cases should be added before the scaling method can be recommended for general use. Highlights: A scaling approach for ducted propeller open water characteristics is presented. Systematic CFD calculations in different scales form the basis of the method. Separate scaling of pressure and friction components is performed. Comparisons with some propulsor configurations show promising results.